2014
DOI: 10.1507/endocrj.ej13-0399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miglitol, vildagliptin, or their combination on serum insulin and peptide YY levels and plasma glucose, cholecystokinin, ghrelin, and obestatin levels

Abstract: α-Glucosidase inhibitors (αGIs) decrease plasma glucose and serum insulin levels in healthy subjects [1,2] and reduce the development of type 2 diabetes in subjects with impaired glucose tolerance (IGT) [3,4]. αGIs reportedly enhance active glucagon-like peptide-1 (GLP-1) responses and reduce total glucosedependent insulinotropic polypeptide (GIP) responses [5][6][7][8]. Dipeptidyl peptidase-4 (DPP-4) inhibitors, such as sitagliptin or vildagliptin, increase active GLP-1 and GIP by inhibiting DPP-4 enzymatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…However, the exact effects of increased active GLP-1 after combination therapy in diabetes patients remain unknown; therefore, further research is needed to study this aspect. Subsequently, the effect of another combination therapy of an αGI and a DPP-4 inhibitor on gut hormones, such as total PYY (PYY 1-36 plus PYY ), CCK, ghrelin, and obestatin, were evaluated (Table 2) [36]. Miglitol and vildagliptin were administered to healthy men either as monotherapy or combination therapy, and the results were compared to those of the control group (no drug).…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact effects of increased active GLP-1 after combination therapy in diabetes patients remain unknown; therefore, further research is needed to study this aspect. Subsequently, the effect of another combination therapy of an αGI and a DPP-4 inhibitor on gut hormones, such as total PYY (PYY 1-36 plus PYY ), CCK, ghrelin, and obestatin, were evaluated (Table 2) [36]. Miglitol and vildagliptin were administered to healthy men either as monotherapy or combination therapy, and the results were compared to those of the control group (no drug).…”
Section: Human Studiesmentioning
confidence: 99%
“…The authors suggested that these effects were due to the increased active GLP-1 levels and improved hyperglycemia by the combination therapy. Combination therapies of three different αGIs (acarbose, voglibose, or miglitol) and sitagliptin were administered to C57BL/6J mice [39], and all three combinations resulted in a synergic increase of Effects of miglitol, sitagliptin, or vildagliptin as monotherapy and combination therapy on postprandial gut hormones in healthy individuals [35,36]. Two arrows represent combination therapy: two upward arrows indicate that combination therapy increased the level of a specific variable compared with monotherapy, while two downward arrows indicate that combination therapy decreased the level of a specific variable compared with monotherapy.…”
Section: Human Studiesmentioning
confidence: 99%
“…An important effect of GLP-1 receptor agonists is a direct action on the brain stem to induce satiety and inhibit gastric emptying [59]. A variety of methods have been used to assess appetite and gastric emptying directly, including rate of ingested glucose into the circulation, surrogates of appetite such as ghrelin and gastrin levels or the paracetamol test of gastric emptying and findings indicate that DPP-4 inhibitors have no effect on satiety and gastric emptying [59,60,[91][92][93][94][95]. The prevailing evidence suggests that the effect of GLP-1 on satiety and gastric emptying requires doses of GLP-1 that are much higher than those achieved by DPP-4 inhibition [94].…”
Section: Integrating the Secondary Pharmacological Effects With The Cmentioning
confidence: 99%
“…For example, H4 changed its position nearly 90°, which lead to three H-bonds interactions between H4, O4 and Gln45, Tyr452 and His148 (Table 4). Actually, multiple hydroxyl groups played a critical role in the stabilization of the miglitol at the catalytic sites of β-glucosidases [46][47][48][49] .…”
Section: Geometrical Conformation Analysis Of Docking Moleculesmentioning
confidence: 99%